Transient Thermal Analysis in an Intermittent Ceramic Kiln with Thermal Insulation: A Theoretical Approach - Ricardo S. Gomez; Túlio R. N. Porto; Hortência L. F. Magalhães; Clotildes A. L. Guedes; Elisiane S. Lima; Dannyelle M. A. Wanderley; Antonio G. B. Lima (Advances in Materials Science and Engineering)
Increasing the thermal efficiency of drying and firing processes of ceramic products plays an important role for industries that want to remain competitive in the market. Thus, this work aims to evaluate the influence of the type and thickness of thermal insulations, applied on the external sidewalls of an intermittent ceramic kiln, on heat transfer, temperature distribution in the insulating material, maximum external surface temperature, and energy gain, compared to the kiln without thermal insulation. All proposed mathematical formulations are based on the energy conservation, and mathematical procedures are implemented in Microsoft Excel software. Here, it was tested four types of thermal isolators: fiberglass, rockwool, calcium silicate, and ceramic fiber. Results indicate that the greater the thickness of the thermal insulation, the lower the maximum external surface temperature and the greater the energy gain when compared to the kiln without thermal insulation. In addition, fiberglass is the insulating material, among the four types analyzed, which provides greater energy gain and greater reduction in maximum external surface temperature.